Properties of Ag-SnO2 Contact Materials for Low-Voltage Electrical Appliances with Different Doped Particle Sizes - Haitao Wang; Mei Zhang; Menglin Yang (Advances in Materials Science and Engineering)
In this paper, the relationship between additive particle size and properties of Ag-SnO2 contact materials was studied. La2O3 and Fe2O3 were selected as additives for contact materials, and the proportion of additives were determined by wettability experiment results; Ag-SnO2 contact materials were successfully fabricated by the powder metallurgy method, and the physical and electrical contact properties of Ag-SnO2 contact materials with five additive particle sizes were investigated. The results show the influence of additives on the properties of Ag-SnO2 contact materials are disparate, the contact resistance and arc energy are smaller and more stable when the additive particle size is about 500 nm. For further proving this conclusion, the arc-eroded surface morphologies of the doped AgSnO2 contact materials were investigated by scanning electron microscopy (SEM), which indicated that the properties of two kinds of Ag-SnO2 contact materials could be improved significantly by selecting appropriate additive particle size.